Performance Analysis of Superconducting Waveguides and Reflector Antennas in Radio Telescopes - Ong, Sing Sean (2016)
In this project, we perform an analysis on two components at the front end of a radio telescope, which are the reflector antenna and waveguide. Waveguide characterization must be implemented in a radio telescope to improve the performance of transmission from the horn to the receiver circuits. The design configuration of the ALMA Cassegrain antenna was applied to detect signal with lower frequency such as 10 GHz. The radiation pattern at the subreflector shows reasonably good results. This proves that the ALMA telescope is able to perform well even with a lower frequency applied onto it. Superconducting waveguides are also proposed to minimize the loss of signal in the transmission system of a radio telescope. Here, Noguchi-Naruse-Sekimoto’s formulation was applied in a superconducting circular waveguides to analyse the loss of signals. The results show that a superconducting waveguide exhibits low but finite loss below the gap frequency. The loss, however, turns out to be higher than normal conducting waveguide when the frequency is above the gap frequency. The higher loss can be attributed to the higher surface resistance and field penetration for superconducting waveguides operating above the gap frequency.